Circulating Tumor Cells Detected in the Tumor‐Draining Pulmonary Vein Are Associated with Disease Recurrence after Surgical Resection of NSCLC. Issue 10 (October 2016) - Crosbie, Phil A.J.; Shah, Rajesh; Krysiak, Piotr; Zhou, Cong; Morris, Karen; Tugwood, Jonathan; Booton, Richard; Blackhall, Fiona; Dive, Caroline
ABSTRACT : N/A: Tumor recurrence after surgical resection of NSCLC obstructs long‐term disease‐free survival in approximately 50% of cases. Our data suggest that combining circulating tumor cell enumeration (as single cells or clusters) in tumor‐draining pulmonary vein and peripheral blood (assessed by CellSearch) at the time of NSCLC surgery better identifies those patients at higher risk for lung cancer recurrence than does peripheral circulating tumor cell number alone.